EASE of USE, CONVENIENCE, TRUST, and INTENTION to USE MOBILE BANKING - Woelandari P.G, Dewi Woelandari P.G Sri; Setyawati, Novita Wahyu; Rianto, Muhammad Richo (Journal of Economic Development, Environment and People, 2022)
Abstract. Technological developments, especially in the banking world, can provide services to their customers, especially in terms of using digital banking services. Digital banking services have changed the way and method of banking operations. Customers and banks use digital banking as a technology-based service delivery channel to increase customer satisfaction. This study aims to apply the technology acceptance model (TAM) to investigate the intention to use mobile banking among millennials. The analytical technique used in this study uses SPSS version 24 software. The survey results indicate that ease of use, convenience, and trust have a significant positive effect on customer interest in using mobile banking.